Perkahwinan campur peranakan Punjabi di Sabah - Sarjit S. Gill, (Universiti Kebangsaan Malaysia, 2001)
This report begins with a definition of the term peranakan. It then goes on to discuss the process that leads to the creation of a peranakan Punjabi society in Sabah, namely through intermarriages among the Sikh men and the local women. This report is based on interviews and fieldwork in April 2001. Observation in four gurdwara undertaken shows that the peranakan Punjabi possess a unique cultural identity that distinguishes them from Sikhs in Peninsular Malaysia. Nevertheless, they display a commitment towards Sikhism